Sentiment Analysis of Transsphenoidal Surgery in the Cushing's Subreddit - Dimitroyannis, Rose; Thodupunoori, Sharanya; Leung, Ringo; Nordgren, Rachel; Polster, Sean P.; Horowitz, Peleg M.; Das, Paramita; Roxbury, Christopher R. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction While the definitive treatment of Cushing's disease (CD) is transsphenoidal surgery (TSS), little is known about patients' perceptions of their treatment experience. Reddit, an online forum, allows users to interact on “subreddits” specific to interests. We aimed to assess patient sentiments regarding TSS for CD on the Cushing's subreddit.Methods Cushing's subreddit posts were sorted by “top” of “all time” to evaluate those with the most engagement throughout the site's history. Posts unrelated to surgical management of CD were excluded. Descriptive statistics were performed to compare pre- and postoperative posters. Sentiment analysis was performed using TextBlob, a Python library, and thematic analysis was done using grounded theory qualitative methods.Results From 68 entries, 53 (77.9%) were written by individuals who underwent TSS. Of posters with a history of TSS, many (68%, n = 25/38) reported difficult recovery, but an overwhelming majority (91.3%, n = 42/46) also reported positive long-term outcomes. Posters who had undergone TSS were more likely to post content with negative sentiment (p = 0.007), often regarding issues with access to the surgery. Thematic analysis revealed general themes of seeking and sharing advice, healthcare access issues, excitement for TSS, short-term symptoms postoperatively, and long-term outcomes.Conclusion This study is the first to utilize Reddit to analyze patient perceptions of TSS for CD. This analysis suggests that most posters feel positively regarding their long-term outcome, while negative sentiments are often related to difficulties accessing care. Further studies should assess access to care for those with CD.
Keywords: sentiment analysis; TSS; Cushing's disease; Reddit